Overcoming multidrug resistance via simultaneous delivery of cytostatic drug and P-glycoprotein inhibitor to cancer cells by HPMA copolymer conjugate. (January 2017) - Sivak, Ladislav; Subr, Vladimir; Tomala, Jakub; Rihova, Blanka; Strohalm, Jiri; Etrych, Tomas; Kovar, Marek
Abstract: Multidrug resistance (MDR) is a common cause of failure in chemotherapy for malignant diseases. MDR is either acquired as a result of previous repeated exposure to cytostatic drugs (P388/MDR cells) or naturally, as some tumors are congenitally resistant to chemotherapy (CT26 cells). One of the most common mechanisms of MDR is upregulation of P-glycoprotein (P-gp) expression. Here, we used HPMA copolymer conjugates, whereby the cytostatic drug doxorubicin (Dox) or the derivative of the P-gp inhibitor reversin 121 (R121) or both were covalently bound through a degradable pH-sensitive hydrazone bond. We proved that R121, when bound to a polymeric carrier, is capable of inhibiting P-gp in P388/MDR cells and sensitizing them in relation to the cytostatic activity of Dox. Conjugate bearing both Dox and R121 was found to be far more potent in P388/MDR cells than conjugate bearing Dox alone or a mixture of conjugates bearing either Dox or R121 when cytostatic activity in vitro, cell cycle arrest, accumulation of Dox in cells and induction of apoptosis were determined. Importantly, conjugate bearing R121 is also effective in vivo as it inhibits P-gp in P388/MDR tumors after intraperitoneal administration, while both the conjugate bearing Dox and R121 induces apoptosis in P388/MDR tumors more effectively than conjugate bearing Dox alone. Only conjugate bearing Dox and R121 significantly inhibited P388/MDR tumor growth and led to the prolonged survival of treated mice. However, the most dramatic antitumor activity of this conjugate was found in the CT26 tumor model where it completely cured six out of eight experimental mice, while conjugate bearing Dox alone cured no mice. Graphical abstract: